Efferocytosis of Pathogen-Infected Cells - Karaji, Niloofar; Sattentau, Quentin J. (Frontiers in Immunology, 2017)
The prompt and efficient clearance of unwanted and abnormal cells by phagocytes is termed efferocytosis, and is crucial for organism development, the maintenance of tissue homeostasis, and regulation of the immune system. Dying cells are recognized by phagocytes through pathways initiated via “find-me” signals, recognition via “eat-me” signals and down-modulation of regulatory “don’t eat-me” signals. Pathogen infection may trigger cell death that drives phagocytic clearance in an immunologically silent, or pro-inflammatory manner, depending on the mode of cell death. In many cases efferocytosis is a mechanism for eliminating pathogens and pathogen-infected cells, however some pathogens have subverted this process and use efferocytic mechanisms to avoid innate immune detection and assist phagocyte infection. In parallel, phagocytes can integrate signals received from infected dying cells to elicit the most appropriate effector response against the infecting pathogen. This review focuses on pathogen-induced cell death signals that drive infected cell recognition and uptake by phagocytes, and the outcomes for the infected target cell, the phagocyte, the pathogen and the host.